2012
DOI: 10.1007/s10517-012-1865-7
|View full text |Cite
|
Sign up to set email alerts
|

Functional Activity of Neutrophils in Diabetes Mellitus and Coronary Heart Disease: Role of Myeloperoxidase in the Development of Oxidative Stress

Abstract: We performed a comparative analysis of functional activity of neutrophils in patients with type 2 diabetes mellitus with and without symptoms of CHD. Enhanced H2O2 production by neutrophils in response to N-formyl-Met-Leu-Phe (fMLP) was found in patients with type 2 diabetes mellitus. In patients with type 2 diabetes mellitus associated with CHD, fMLP-induced release of myeloperoxidase from azurophilic granules of neutrophils was reduced and plasma myeloperoxidase level was elevated. Increased peroxidase activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 8 publications
1
19
0
3
Order By: Relevance
“…While "parainflammation" may help to maintain homeostasis, persistent and prolonged diabetes may to occlusion and non-perfusion (Valle et al, 2013). It is interesting to note that in the advanced stages of diabetic retinopathy, the systemic neutrophil count is increased (Woo et al, 2011) and these cells express higher levels of myeloperoxidase and produce more hydrogen peroxide compared to cells from non-diabetic controls (Gorudko et al, 2012). Circulating monocytes are also activated in T1D patients (Josefsen et al, 1994) and they express elevated adhesion molecules (Bouma et al, 2004) with concomitant binding to endothelium (Devaraj et al, 2011).…”
Section: D Inflammation and Immune Cell Activation In Diabetic Retimentioning
confidence: 99%
“…While "parainflammation" may help to maintain homeostasis, persistent and prolonged diabetes may to occlusion and non-perfusion (Valle et al, 2013). It is interesting to note that in the advanced stages of diabetic retinopathy, the systemic neutrophil count is increased (Woo et al, 2011) and these cells express higher levels of myeloperoxidase and produce more hydrogen peroxide compared to cells from non-diabetic controls (Gorudko et al, 2012). Circulating monocytes are also activated in T1D patients (Josefsen et al, 1994) and they express elevated adhesion molecules (Bouma et al, 2004) with concomitant binding to endothelium (Devaraj et al, 2011).…”
Section: D Inflammation and Immune Cell Activation In Diabetic Retimentioning
confidence: 99%
“…-Elevated levels of soluble forms of CAMs -Activated monocytes in diabetic subjects [210][211][212] -Increased circulating neutrophil levels in late-stage diabetic retinopathy [213] The neutrophils express more myeloperoxidase (MPO), and generate greater amounts of cytotoxic hydrogen peroxide in diabetic than in non-diabetic subjects [214].…”
Section: Inflammationmentioning
confidence: 99%
“…[10,11] Highly reactive hypohalous acids formed in the system of Н 2 О 2 -MPО and their derivatives -secondary RHS along with ROS and reactive nitrogen species -determine the efficacy of the cellular response under induction and maintenance of inflammation, [10] thus providing the interrelation between oxidative and halogenating stress. [11] The main source of ROS and RHS is primed neutrophilic leukocytes [12] depositing MPO in azurophilic granules and secreting the enzyme into extracellular media through degranulation. [10] In our previous studies we found the elevated level of MPO activity is associated with high intensiveness of degranulation and destruction of leukocytes in IS of asthma patients with AHR to hypoosmotic and cold triggers.…”
Section: Introductionmentioning
confidence: 99%